Réponses

  • Utilisateur Brainly
2013-12-23T14:00:50+01:00
1) cf COURS...

2) A=(6x+4)²=36x²+48x+16
B=(5x-3)²=25x²-30x+9
C=(2x+3)²-(4x+1)(2x-4)
 =4x²+12x+9-8x²+14x+4
 =-4x²+26x+13
D=-4(4x-4)=-16x+16

3) A=-2x²+5x=x(5-2x)
B=(2x+5)²-81=(2x+14)(2x-4)=4(x-7)(x-2)
C=(x+2)(x+3)+4(x+2)=(x+2)(x+7)

4) -2x²+5x=0 donne x=0 ou x=2,5
4x-5=6-2x donne x=11/6
(2x+3)(5-x)=0 donne x=5 ou x=-1,5

5) 2/3+5/3:(2/7)=2/3+5/3x7/2=13/2
(5/3+1/2):(-6/5)=13/6x(-5/6)=-85/36
2013-12-23T14:28:42+01:00
Bonjour

1) (a+b)² = a² +2ab +b²
(a-b)² = a² - 2ab +b²
(a+b)(a-b) = a² -b²

2) (6x+4)² = 36x² +48x +16
(5x-3)² = 25x² - 30x +9
(2x+3)² - (4x+1)(2x-4) = 4x² +12x +9 - (8x² -16x +2x -4) = 4x² +12x +9 -8x² +16x -2x +4
= -4x² +28x  +13
-4(4x-4) = -16x +16

3) A = 2x² -5x  = x(2x -5)
B = (2x+5)² -81 = ( (2x+5 +9)(2x+5-9) = (2x +14)( 2x -4)
C = (x+2)(x+3) + 4 (x+2)
(x+2)(x+3) +4
(x+2)(x+3+4) = (x+2)(x+7)

4) si x = 5
50 - 25 = 0
25 = 0
donc 5 n'est pas solution de l'équation

-4x-5 = 6 -2x
-4x +2x = 6 +5
-2x = 11
x = -11/2

(2x+3)(5-x) = 0
soit 2x+3 = 0 donc 2x = -3 et x = -3/2
soit 5-x = 0 et -x = -5 ou x =5


5) A = 2/3 +5/3 : 2/7
A = 2/3 +5/3 x 7/2
A = 2/3 + 35/6
A = 4/6 +35/6 = 39/6 = 13/2

B = (5/3 + 1/2) : -6/5
B = (10/6 + 3/6) : - 6/5
B = 13/6 x -5/6
B =  - 65/36

Bon Noël